2013
DOI: 10.1016/j.janxdis.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, thought content, and anxiety on suppression of intrusive thoughts

Abstract: Understanding differences in responses following attempts to suppress versus simply monitor intrusive thoughts is important given the established relationship between intrusive thinking and numerous forms of psychopathology. Moreover, these differences may vary as a function of age. Because of the links between aging and both enhancement in emotion regulation skills and decline in inhibition skills, older and younger adults were expected to differ in their responses (e.g., experience of negative affect and tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 65 publications
1
15
2
Order By: Relevance
“…In contrast, older adults’ negative affect began lower than that of younger adults, but both age groups showed similar increases and subsequent recoveries in negative affect after the introduction of an intrusive thought. In the other behavioral study, which focused only on negative affect among non-clinical individuals, older adults did not differ from younger adults in their overall level of negative affect, but did show a trend toward greater stability of their negative affect across an extended sequence of intrusive thoughts (Beadel, Green, Hosseinbor, & Teachman, 2013). Finally, in studies examining retrospective, self-reported summaries of daily experiences with intrusive thoughts, negative affect appeared to be less tied to one’s level of intrusive thoughts with older age (Brose, Schmiedek, Lövdén, & Lindenberger, 2011), although there is still a relationship among older adults (Stawski, Mogle, & Sliwinski, 2011).…”
Section: Evidence Of Age Differences In Experiences With Intrusive Thmentioning
confidence: 88%
See 4 more Smart Citations
“…In contrast, older adults’ negative affect began lower than that of younger adults, but both age groups showed similar increases and subsequent recoveries in negative affect after the introduction of an intrusive thought. In the other behavioral study, which focused only on negative affect among non-clinical individuals, older adults did not differ from younger adults in their overall level of negative affect, but did show a trend toward greater stability of their negative affect across an extended sequence of intrusive thoughts (Beadel, Green, Hosseinbor, & Teachman, 2013). Finally, in studies examining retrospective, self-reported summaries of daily experiences with intrusive thoughts, negative affect appeared to be less tied to one’s level of intrusive thoughts with older age (Brose, Schmiedek, Lövdén, & Lindenberger, 2011), although there is still a relationship among older adults (Stawski, Mogle, & Sliwinski, 2011).…”
Section: Evidence Of Age Differences In Experiences With Intrusive Thmentioning
confidence: 88%
“…Given that the experimental thought used in this study is perceived as highly negative across ages, the results may have been different if we had introduced intrusive thoughts that varied in their relevance and/or negativity to older versus younger adults (Beadel et al, 2013). Additionally, there may have been other contributors to negative affect in this study besides the recurrence of the intrusive thought, such as participants disliking the task rather than the return of the thought itself.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations